A Complement of Collaborators: Bringing Private Memoirs to Public Life. (3rd May 2016) - Bloom, Lynn Z.
ABSTRACT: This essay focuses on the genesis, growth, development, editing, and publication process of memoirs in their life context. It demonstrates how the efforts of a full complement of collaborators, from editors to web designers—some conspicuous, others unobtrusive, but all significant—are necessary in bringing an autobiographical work to autonomous existence.